Effects of highly cushioned and resilient racing shoes on running economy at slower running speeds - Joubert, D. P.; Dominy, T. A.; Burns, G. T. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The Nike Vaporfly line of running shoes improves running economy by ~2.7% to 4.2% at running speeds of 13 to 18 km·h-1. It is unclear whether similar benefits are conferred at slower speeds. Our purpose was to determine the effects of the Nike ZoomX Vaporfly Next% 2 (VFN2) on running economy at 10 and 12 km·h-1 compared with a mass-matched control (CTRL) shoe.